Experiences of Workplace Violence among Nursing Personnel in Rapti Sub-regional Hospital, Dang District, Western Nepal - Shrestha, Durga Laxmi; KC, Ishwori; Panth, Asha (Journal of Advanced Academic Research, 2022)
Background: Workplace violence against (WPV) health care workers is a common and widespread phenomenon. This problem is already high and still continuously increasing. The objective of the study was to explore the experience of workplace violence among nursing personnel. Methods: A purposive sampling technique was used to select 20 nursing personnel. The qualitative data was generated by using guidelines for (i) Focus group Discussion (FGD), (ii) in- depth interview and (iii) key informant interview. Three FGD were conducted: two groups of staff nurses and one group of ANM, tape recording as well as field note was maintained. In-depth interviews were conducted with 4 nursing personnel who had experienced of workplace violence (WPV), the facial expressions, gesture, tone of voice and emotion experienced by respondents were observed during data collection. Two key informant interviews were carried out among organizational chiefs (medical superintendent) to verify the findings. Results: All participants had experienced some types of abuse in their lifetime and majority of them had experienced verbal abuse in their workplace, where the perpetrators were team i.e. particularly by doctors. The nature of verbal abuse was insult, threatening and scolding in front of patients and visitors and majority of them reported the common place of violence was maternity ward particularly during night duty. The common cause behind the WPV was due to absence of policy to punish the perpetrators. Among the abused personnel, majority of them reported psychosomatic problems: anorexia, insomnia and depression. The studies revealed that majority of respondents were seeking immediate support from colleagues. In term of preventive measures, majority of respondents reported to give training on self-protection, staffs counseling for abused and developing violence prevention policy in the workplace. Conclusion: Based on the identified qualitative information, the four themes were developed: low morale, low responsiveness, lack of unity and hazardous work environment which were responsible for increment of WPV. Therefore there identified themes need to be taken in consideration for the violence prevention policy should be developed in the concerned areas to control and prevent the WPV.